Eksistensi Masjid Asasi Terhadap Perkembangan Pendidikan di Pesantren Thawalib Gunung Kota Padang Panjang - Beti, Leli Indra; Yahdy, Genta Vebdilla; Mardianto, Pisdoni (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2024)
The aim of this research is to describe the developments that have occurred at the Thawalib Gunung Islamic Boarding School and the relationship between the Islamic boarding school and the Asasi Mosque in Padang Panjang City. This research is historical research which consists of four stages with steps: heuristics, source criticism, synthesis, and writing. Apart from using archives, this research uses data collected through interviews and observations. The conclusion of the research shows that the Thawalib Gunung Islamic Boarding School was founded on April 21 1921 with the name Islamic Islamic Boarding School, the forerunner to the establishment of this Islamic Boarding School was inseparable from the influence of Surau Asasi which at that time was established in the Gunung area of ​​Padang Panjang City. Asasi Mosque as a place of education is to provide religious knowledge, especially for the sons and daughters of the Nagari Gunung community. From a mosque, the community wanted the establishment of an Islamic boarding school with the name Pondok Pesantren Thawalib Gunung.